Association of Glycemic Status and Admission Serum Troponin-I Level in Acute ST-Elevation Myocardial Infarction (Community Based Medical Journal, 2026)
A cross-sectional, analytical study was conducted in Mymensingh Medical College Hospital, Mymensingh, Bangladesh, between January and December of 2021, to observe glycemic status in patients of acute ST-elevation myocardial infarction and its association with admission serum troponin-I level. Patients were recruited from the Department of Cardiology. All physical parameters were studied and recorded in the Department of Cardiology, while the biochemical tests were done in the Department of Physiology of the same institution. A total of 70 patients having acute ST-elevation myocardial infarction participated in this study. They were grouped as control group (Group-I) i.e., normoglycemic, and study group (Group-II) i.e., hyperglycemic but non-diabetic. Patients’ general (demographic) information, personal history, physical parameters, i.e., height, weight, BMI, temperature, pulse, systolic and diastolic blood pressure, results of biochemical tests (e.g., serum troponin-I, random plasma glucose, and HbA1c), and ECG reports were recorded. Serum troponin-I, random plasma glucose and HbA1c were measured using Time-resolved Fluorescence Immunoassay Autoanalyzer. Serum troponin-I levels during admission were found 11.65±8.38 ng/ml and 21.75±9.53 ng/ml in group I and group II respectively (p